KARAKTERISTIK KEPENULISAN ARTIKEL PADA JURNAL AGRISEP UNIVERSITAS BENGKULU TAHUN 2015-2019 MENGGUNAKAN KAJIAN BIBLIOMETRIKA - Zendrato, Bezisokhi; Purwaka, Purwaka; Samosir, Fransiska (Direktorat Repositori, Multimedia, dan Penerbitan Ilmiah - Badan Riset dan Inovasi Nasional (BRIN Publishing), 2021)
The purpose of this study is to know the characteristics of authorship and articles in the Journal AGRISEP at University of Bengkulu in 2015-2019 by using a study of bibliometrics based on several indicators. This research uses a descriptive quantitative study. The object is articles in the AGRISEP Journal of University of bengkulu in 2015-2019 with a total of 91 articles. Data were analyzed by using frequency tabulations. The results of this research show that the characteristics of writing and articles in the Journal of University of Bengkulu AGRISEP in 2015-2019 is vary greatly. It shows that the authors were male (54.08%). Most of the authors work as Lecturers (50.43%.). University of bengkulu contributed the most articles with almost 41 articles. Article was written by 3 authors (52.75%). Most of the authors have Master educational background. Articles use Indonesian language (96.70%.). The highest author's productivity is Sriyoto. The length of articles contain in this journal was 11-15 pages (56.15%). Articles contain 3 keywords were 51.14%, and the abstract length is around 150-199 words (35.16%). The most type of literature is Journal with 373 citations (36.93%). Based on these characteristics, it can be seen that the articles have met the written guidelines and articles that have been determined as well as an overview of the development of the articles in the AGRISEP Journal of Bengkulu University in 2015-2019.